DESIGN OF A CREATIVE CENTER BUILDING USING A GREEN ARCHITECTURE APPROACH IN THE BOGOR AREA - Dian Kusumowardani; Aristia Aristia; Medina Suci Handayani; Tri Wahyuni; Selly Indrawati; Ksatria Dwitama (Jurnal Ilmiah METADATA, 2026)
Climate change and public awareness of the environment are increasingly driving interest in environmentally friendly building design, including in Indonesia. This study examines the design of a Creative Center building using a green architecture approach in the Bogor area. The primary focus of this study is to explore how to apply green architecture principles to create an efficient, environmentally friendly building that supports the creative process. An analysis was conducted to identify relevant green architecture elements, such as energy efficiency, the use of environmentally friendly materials, water management, and the utilization of green open spaces. The study results indicate that the application of green architecture to the Creative Center building in Bogor can improve the building's environmental quality and provide long-term economic benefits. The study concludes that the design of the Creative Center building using a green architecture approach not only supports environmental sustainability but also creates a creative and useful space for the community.